Emergency department nurses’ competences: implementing a personal dossier for nurses onboarding, skills maintenance, and quality audit - Marco Ruggeri; Laura Rasero; Angela Brandi; Stefano Bambi (Infermieristica Journal, 2023)
Emergency Departments (EDs) are among the most challenging clinical settings for nurses. EDs are complex settings, including patients with various clinical severity levels, every typology of medical and surgical specialties, fast organizational responses, a triage area to identify the clinical priorities to access a medical visitation, and simultaneous emergency codes to be managed. Therefore, the issue of acquiring and maintaining adequate competencies to manage the delivery of nursing care in a multifaceted setting such as ED is central.